Levels of Maternal Care Verification Pilot: Translating Guidance Into Practice. Issue 6 (December 2018) - Zahn, Christopher M.; Remick, Arlene; Catalano, Andrea; Goodman, David; Kilpatrick, Sarah J.; Menard, M. Kathryn
Abstract : Development of systems for perinatal regionalization and for the provision of risk-appropriate maternal care is a key strategy to decrease maternal morbidity and mortality. Regionalized systems pertaining to neonatal care are broadly implemented in many states, but networks for risk-appropriate maternal care are lacking. In response to increases in maternal morbidity and mortality over the past decade, the American College of Obstetricians and Gynecologists (ACOG) and the Society for Maternal-Fetal Medicine (SMFM) developed and published the levels of maternal care guidelines in 2015. The guidelines are designed to promote collaboration among maternal facilities and health care providers with the goal that pregnant women receive care at a facility appropriate for their risk. The Centers for Disease Control and Prevention (CDC) developed the Levels of Care Assessment Tool in 2013 to assist states and jurisdictions in assessing maternal and neonatal levels of care in alignment with the national guidelines published by ACOG and SMFM and the American Academy of Pediatrics, respectively. With the goal of promoting levels of maternal care, ACOG and SMFM developed and piloted the levels of maternal care verification program. Fourteen facilities across three states (Georgia, Illinois, and Wyoming) participated in the pilot. A multidisciplinary team representing organizations with expertise in maternal risk-appropriate care performed an onsite comprehensive review of the maternal services available in each facility using the results from the CDC Levels of Care Assessment Tool as a previsit screening. A verification program that could be implemented on a local, state, or regional scale is being developed leveraging the lessons learned from the pilot. Abstract : In piloting the levels of maternal care verification program, we demonstrated the ability to implement a levels of care program on a broad scale.